Evaluation of sleep position shifts in patients with obstructive sleep apnea syndrome with the use of a mandibular advancement device - Ciavarella, Domenico; Ferrara, Donatella; Fanelli, Carlotta; Montaruli, Graziano; Burlon, Giuseppe; Laurenziello, Michele; Lo Russo, Lucio; Esperouz, Fariba; Tepedino, Michele; Lorusso, Mauro (Frontiers in Dental Medicine, 2025)
BackgroundThe aim of this study was to evaluate position shifts during sleep of patients with obstructive sleep apnea (OSA) syndrome both with and without the use of a mandibular advancement device (MAD).MethodsIn total, 73 adult Caucasian patients diagnosed with obstructive sleep apnea syndrome confirmed by polysomnography were retrospectively enrolled. Inclusion criteria were as follows: age >20 years, body mass index <34 kg/m2, polysomnographic diagnosis of OSA, non-smoker, absence of comorbidities at diagnosis, and treatment with a MAD. Two polysomnographic monitoring were performed: one at the time of diagnosis (T0) and another after 3 months of treatment (T1). The parameters evaluated were the apnea-hypopnea index, oxygen desaturation index, the total number of position shifts, and position shift index (number of shifts per hour). Since the variables failed the normality test, the Wilcoxon test was performed to analyze the correlation between the mean of polysomnographic parameters at T0 and T1. The difference between the T1 and T0 values for each variable was evaluated using Spearman's rho correlation test. Statistical significance was set at p < 0.05.Results and conclusionsAll the parameters, including respiratory and positional measures, were significantly reduced after the use of a MAD compared to the beginning. Spearman’s correlation test revealed a relationship between the total number of sleep position shifts and the sleep position shift index with the oxygen desaturation index. However, no significant correlation was observed between the apnea-hypopnea index and the positional values.